Efeitos da remoç\~ao de tarifas e barreiras n\~ao tarifárias na cadeia produtiva do leite em pó no Brasil - Krisley Mendes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Milk is one of the few agricultural products in which Brazil is not competitive. The domestic market is served by domestic production and imports from Argentina and Uruguay. The Mercosur-European Union bi-regional Association Agreement predict the elimination of tariffs and the harmonization of non-tariff measures (MNTs) between them. Given that the EU is one of the most competitive regions in the world market for powdered milk, this study analyzes the effects of the agreement on the links in this production chain in the Brazilian market. For this, a constant, nested, multisectoral and vertically integrated elasticity of substitution model is structured and incorporates uncertainty in the Armington elasticities through Monte Carlo simulations, as in Hallren and Opanasets (2018). The model allows decompose the effect in relative prices (Armington effect) and what we call the preference effect in the market shares of Brazil, Mercosur and the EU in the different production stages. The analysis is carried out in three scenarios: removal of tariffs, removal of MNTs, and removal of tariff and MNTs concomitantly. The results show that the elimination of the tariff would make Brazil lose 6.7 percentage points in its downstream market share, Mercosur would lose 1 percentage point of its current market share and the EU would participate in the Brazilian market with 8.2%. The national agricultural link would lose 1.42% of demand from Brazilian dairy. When only MNTs are removed, the Brazilian market share is reduced by 51.16 percentage points, in the most conservative estimate. This measure would favor Mercosur, which would increase its participation by 49.42 percentage points, while the EU would participate with 2.23%. The concomitant removal of tariffs and MNTs would make Brazil lose 71.7 percentage points in the domestic market, in the most conservative hypothesis. This means reducing production by 475 thousand tons of powdered milk. The domestic agricultural link would lose 15% of current dairy demand. The loss occurs benefiting the EU, which would see 58.75 points increase in downstream market share. Mercosur would add 13.41 percentage points to its current dowstream market share.
10419/284872
Keywords: F13; F1; 330; powdered milk; trade opening; dairy; Brazil; European Union